TERORRIST PROPAGANDA ON THE INETRNET (Heritage, 2020)
The exchange of large amount of data contributed to making information technologies an integral part of the modern world, often shaping public opinion, whether through its using, or abusing. In such a sense, modern terrorism uses or abuses various possibilities of information technologies, especially Internet, for the promotion of its own activities, as well as for the recruitment. Internet usage made the eradiation of terrorism propaganda such an easy task, so Internet practically became overwhelmed by it. Attitudes and threats expressed by terrorists that put their opponents under serious pressure, as well as recruitment of new members has contributed to to an increase in the number of terrorist groups that abuse the Internet for media purposes. Additional problems stem from the impossibility of their effective and timely control in a bid to prevent abuse aimed at terrorist propaganda, but also from the fact that most propaganda activities can neither be prevented nor limited in time, since such preventions and limitations infringe human rights, such as freedom of expression, religion and others. Since propaganda itself is not prohibited, the use of propaganda for promotion, financing, recruitment, training and commission of terrorism purposes is characterized as a criminal offense. In accordance with the European legislation, in order to provide evidence of incitement to terrorism, the connection between intent and direct causality has to be specified between the alleged propaganda, actual conspiracy or commission of terrorist acts.In this regard, the aim of this paper is to point out to danger of terrorist propaganda on the Internet, as well as to its types of manifestations (symbols) in an attempt to identify it in a timely manner and to curtail it in an adequate way.
Keywords: errorism, Internet, Terrorist Propaganda, Types of Manifestations, Features